Molecular Interactions for the Curcumin-Polymer Complex with Enhanced Anti-Inflammatory Effects - Yan He; Hongfei Liu; Wangqing Bian; Yue Liu; Xinyang Liu; Shijing Ma; Xi Zheng; Zhiyun Du; Kun Zhang; Defang Ouyang (MDPI AG, 2019)
The molecular interactions between compound and polymeric carriers are expected to highly contribute to high drug load and good physical stability of solid dispersions. In this study, a series of amorphous solid dispersions (ASD) of Curcumin (Cur) were prepared with different polymers by the solvent evaporation method. With the carrier polyvinylpyrrolidone (PVP), the amorphous solid dispersion system exhibits a better solubility and stability than that with poloxamers and HP-β-CD due to the strong drug-polymer interaction. The drug/polymer interaction and their binding sites were investigated by combined experimental (XRD, DSC, FTIR, SEM, Raman, and 1H-NMR) and molecular dynamics simulation techniques. The Curcumin ASD demonstrated enhanced bioavailability by 11-fold and improved anti-inflammatory activities by the decrease in cytokine production (MMP-9, IL-1β, IL-6, VEGF, MIP-2, and TNF-α) compared to the raw Curcumin. The integration of experimental and modeling techniques is a powerful tool for the rational design of formulation development.